2019
DOI: 10.2298/csis190122008j
|View full text |Cite
|
Sign up to set email alerts
|

Logical filter approach for early stage cyber-attack detection

Abstract: The planned in advance cyber-attacks cause the most damage for the users of the information systems. Such attacks can take a very long time, require considerable financial and human resources, and therefore, they can only be organized by large interest groups. Furthermore, current intrusion detection systems, intrusion prevention systems and intrusion response systems used to protect against cyber-attacks have several shortcomings. Such systems respond only to the attack itself when it is too late to take a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…ML techniques have a substantial contribution to detecting different types of intrusions on network and host computers. However, there are numerous areas such as detection of zero-day and new attacks are considered significant challenges for ML techniques [32].…”
Section: Introductionmentioning
confidence: 99%
“…ML techniques have a substantial contribution to detecting different types of intrusions on network and host computers. However, there are numerous areas such as detection of zero-day and new attacks are considered significant challenges for ML techniques [32].…”
Section: Introductionmentioning
confidence: 99%
“…Machine Learning technology has a significant impact on the detection of different forms of network and host computer breaches. Numerous sectors are, nevertheless, considered as important problems for ML methods as zero-day detection and novel assaults (Jusas et al, 2019). Cyber defense systems may use a combination of approaches to prevent data breaches.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Early detection requires the detailed monitoring of network and system parameters in order to be able to accurately identify the early stages of an attack when it is still possible to destroy the attack chain. Jusas V., Japertas S., Baksys T. and Bhandari S., in [22], proposed considering a chain of attacks consisting of nine stages, as well as a method for detecting cyberattacks at an early stage based on an analysis of the chain of attacks using hardware implementation of logical filters. The authors' experiment confirmed the possibility of detecting an attack at an early stage.…”
Section: Brief Overview Of Used Articlesmentioning
confidence: 99%